APOLOGETIKA IRENEUS KEPADA KAUM BIDAT YANG MEMPERTENTANGKAN KEILAHIAN YESUS - Meriwati; Tjutjun Setiawan (Manna Rafflesia, 2024)
Topics about the Trinity, Christology, as well as topics about heretics are always debatable topics. It's not only happening at the present time but has also started since the first centuries, during the time of the church fathers. Irenaeus is a Christian figure who is known as the father of the church, also at the time when he was dealing with the teachings of Gnosticism, and how was Irenaeus’ view in dealing with Gnosticism as well as explaining Christology. This article is a descriptive description of Irenaeus' Christology as a contrast to the development of Gnostic Christology in the second century AD, so the method used is descriptive qualitative. The purpose of this article is so that Christians can understand Christology correctly. This article is not only meant to be a historical depiction, but also to show its continuity with the post-Enlightenment Christological dynamics as proposed by William Bousset who attempted to place Paul's Christology in the context of Gnosticism.